Identification оf World Class Universities - E. V. Balatsky; N. A. Ekimova (Мир новой экономики, 2018)
The article discusses the concept of world-class universities and the author’s understanding of the term, allowing not only to identify these objects but also to quantify their international potential. The hypothesis that education is a “secondary” function of society and follows on the success and needs of the real economy. Based on ranking of QS company the analysis of the international positions of the leading universities of countries belonging to BRICS and states of African, Latin America and Asia. The reference point was used at Harvard University. The analysis excluded the countries of the British Commonwealth and the United States, which unconditionally dominating in all Global University rankings. It is shown that Russia today has only one world-class University - the Moscow state University. M. V. Lomonosov, which has the most simple among all the identified universities of this kind. Revealed weaknesses of the domestic University system.